93 Unexplained pulmonary hypertension in black women living with hiv (BWLWH): H-art to heart sub-study. (17th July 2020) - Manmathan, Gavin; Ngwu, Nnenna; Johnson, James; Hemat, Nargis; Chacko, Liza; Little, Callum; Barber, Tristan; Kinloch, Sabine; Madge, Sara; Kotecha, Tushar; Burns, Fiona; Johnson, Margaret; et al.
Abstract : Introduction: 37.9 million people worldwide are living with HIV (human immunodeficiency virus), acquired immune deficiency syndrome (AIDS)-related deaths have reduced by 51% since the peak in 2004. 42% of those infected are BWLWH yet represent only 9% of those included in clinical trials. HIV/AIDS has been shown to be associated with the development of heart failure, pulmonary hypertension and myocarditis. Previous studies in asymptomatic PLWH have revealed a high burden of underlying CVD and subclinical myocardial inflammation as detected by CMR. The H-ART to Heart study is designed to examine the burden of cardiovascular disease (CVD) in asymptomatic PLWH compared to HIV negative controls (-) excluding traditional CV risk factors. Methods: A cross-sectional study comparing asymptomatic BWLWH aged 35-55yrs (diagnosed >10 yrs, with undetectable viral loads) to HIV negative controls. Black African/Caribbean women without known CV risk factors (hypertension, hyperlipidaemia, diabetes, smoking, inflammatory arthritis, depression, severe mental illness) or hepatitis co-infection were included. Assessment included blood pressure (BP), bloods including NT-ProBNP. Echocardiography was performed in all participants and stress perfusion CMR with multiparametric mapping for BWLWH. We compared CMR results with a previously selected control group. Results: 48 participants have been recruited (23 BWLWH, 25 controls; mean age 47.7±4.1 v 44.7±6.2yrs, P=0.06; mean BP 125/77 v 123/79mmHg), mean results for BWLWH were as follows: duration of HIV 17.6±6.2 yrs, duration of ART 11.5±5.2 yrs, nadir CD4 count 262±158 cells/μL, current CD4 count 662±188 cells/μL and current viral load <40 copies/mL . There were no significant differences in baseline data (Table 1 ) apart from higher mean cLDL (3.49±1.22 v 2.42±0.74, p=0.02) and median CRP (3(2, 6) v 1(1, 3), p=0.042) in BWLWH, as well as a trend towards higher median NT-proBNP (147 (108, 153) v 65.5(59.5, 73.8)ng/L). Echocardiogram parameters were similar between groups, however there was a trend to higher LA volumes in BWLWH (48.16±10.09 v 42.09±11.56, p=0.126) and similar prevalence of detectable tricuspid regurgitation leading to a significantly elevated estimated Pulmonary Artery Pressure (PAP) in BWLWH (27.7 v 21.2mmHg, p=0.016). Interestingly BWLWH had higher mean LVEF%(Simpson's Biplane) than controls (Table 1 ). A MRI sub-study data showed no difference in LV mass, LVEDV, T1, T2 with no evidence of ischaemia or myocarditis between the groups, although number are small (Table 2 ). Conclusion: Preliminary data from our study of asymptomatic low risk BWLWH without traditional CVD risk factors removed indicates raised PAP which cannot be explained by hypertension, diastolic dysfunction, ischaemia or previous myocarditis. The cause of the raised PAP is unclear and requires further investigation. Whether this finding is of importance in CV risk assessment of BWLWH remains to be seen. Conflict of Interest: None